2002
DOI: 10.1200/jco.2002.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Paclitaxel and Concurrent Rapid-Fractionation Radiation for Resectable Pancreatic Adenocarcinoma: Toxicities, Histologic Response Rates, and Event-Free Outcome

Abstract: Preoperative paclitaxel-based concurrent chemoradiation is feasible. The toxicity of this regimen seems greater than that with fluorouracil. The histologic responses and survival are similar, suggesting no advantages to paclitaxel-based preoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(66 citation statements)
references
References 32 publications
1
63
0
2
Order By: Relevance
“…Despite significant improvements in operative techniques and mortality rates related to pancreatectomy and the advance of adjuvant chemoradiation therapy, the prognosis for patients with PDA remains unchanged in the last four decades. Neoadjuvant CRT has been increasingly used in patients with potentially resectable PDA and has been shown to improve the survival and locoregional metastatic disease [15,[20][21][22][23]. In this group of patients, the frequency of pCR in subsequent pancreatectomy specimens is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in operative techniques and mortality rates related to pancreatectomy and the advance of adjuvant chemoradiation therapy, the prognosis for patients with PDA remains unchanged in the last four decades. Neoadjuvant CRT has been increasingly used in patients with potentially resectable PDA and has been shown to improve the survival and locoregional metastatic disease [15,[20][21][22][23]. In this group of patients, the frequency of pCR in subsequent pancreatectomy specimens is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2 Thus, the application of radiosensitizing drugs with concurrent irradiation of the tumor bed, that is, chemoradiation, is being investigated as a primary treatment for locally advanced, unresectable pancreatic cancer, 10 -12,40,41 as well as a neoadjuvant procedure for downstaging of tumor to the point where surgical resection may be feasible. [42][43][44] Although few patients are deemed to have resectable disease, recent studies have suggested that these patients may also benefit from a program of preoperative chemoradiation. [3][4][5][6][7][8][9] Those patients given preoperative chemoradiation had significantly higher numbers of disease-free margins and fewer numbers of involved lymph nodes at surgery than their counterparts treated with "curative resection" alone.…”
Section: Discussionmentioning
confidence: 99%
“…All trials report that neoadjuvant therapy is well tolerated and feasible to administer 17,19,20,32,46 , and patients receive earlier exposure to systemic therapy and treatment for micrometastatic disease. The downside of the approach is that surgery for nonresponders must be delayed, and if the lack of response continues, patients might progress to an unresectable state.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A small trial of neoadjuvant chemotherapy with paclitaxel and radiation, combined with intraoperative electron-beam radiation therapy, reported that the regimen was feasible 20 . Of 35 patients, 25 underwent laparotomy, with 5 being found to have unresectable disease.…”
Section: Neoadjuvant Therapy In Primary Resectable Tumoursmentioning
confidence: 99%